Biomass Production and Biomass Relationship of Young Callicarpa pentandra - Tsai, Lim Meng (1991)
Callicarpa pentandra is a common tree of Malaysian secondary forests. The biomass of six-year-old trees from a shifting agriculture fallow was determined and biomass regressions were obtained. Biomass of the plots was estimated using the regressions. The total tree biomass of the stand was estimated at 44 t/ha, comprising2.7 t leaf, 8.5 t branch and 32. 6t stem.